Association between five polymorphisms in vascular endothelial growth factor gene and urinary bladder cancer risk: A systematic review and meta-analysis involving 6671 subjects - Song, Yuxuan; Yang, Yongjiao; Liu, Li; Liu, Xiaoqiang (Gene, 2019)
Vascular endothelial growth factor (VEGF) gene plays a key role in angiogenesis and tumor growth. The relationship between VEGF gene polymorphisms and bladder cancer (BCa) risk was studied extensively in recent years. However, the currently available results are controversial. To ascertain whether VEGF polymorphisms are associated with the susceptibility to BCa, we conducted this systematic review and meta-analysis. Relevant studies were collected systemically from PubMed, Medline, Embase, Web of Science databases and the Cochrane Library. Odds ratios (ORs) and 95% confidence intervals (CIs) were evaluated using random or fixed effects models by Stata statistical software. This systematic review protocol was registered at International prospective register of systematic reviews (PROSPERO) under number CRD42018099279. A total of eight articles including twenty case-control studies with 3206 BCa cases and 3645 controls were enrolled for this meta-analysis. By pooling all eligible studies, we found that rs3025039, rs833052 and rs25648 polymorphisms were significantly associated with BCa risk. However, in subgroup analyses by stage, we identified a decreased association between the rs699947 A-allele and Muscle-invasive Bladder Cancer (MIBC) under allele contrast, homozygous and recessive genetic models (A vs C: OR = 0.76; AA vs CC: OR = 0.49, 95%CI = 0.27–0.90, I2 = 0.0%, P = 0.021; AA vs CA + CC: OR = 0.60, 95%CI = 0.38–0.96, I2 = 0.0%, P = 0.034). As to ethnicity subgroup analysis, rs699947 and rs3025039 polymorphisms were thought as a risk factor for BCa risk in Asian population, while a decreased association was revealed between rs699947 (C > A) A-allele and BCa risk in African population under dominant, recessive, homozygous, heterozygous and allele contrast genetic models. While for other polymorphisms, null results were found. Our meta-analysis suggested that rs3025039 (C > T), rs833052 (C > A) and rs25648 (C > T) polymorphisms of VEGF gene increased susceptibility to BCa risk. And our study also demonstrated homozygous TT genotype in rs3025039, homozygous AA genotype in rs833052 and homozygous TT genotype in rs25648 were significantly relevant to elevated BCa risk. In the meanwhile, it is worth noting that rs699947 (C > A) A-allele should be thought as a protective factor for MIBC. •Rs3025039, rs833052 and rs25648 polymorphisms increased BCa risk.•Rs699947 A-allele should be a protective factor for MIBC.